2006
DOI: 10.1002/cne.21159
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of neuropeptide S receptor mRNA and neurochemical characteristics of neuropeptide S‐expressing neurons in the rat brain

Abstract: Neuropeptide S (NPS) and its receptor (NPSR) constitute a novel neuropeptide system that is involved in regulating arousal and anxiety. The NPS precursor mRNA is highly expressed in a previously undescribed group of neurons located between the locus coeruleus (LC) and Barrington's nucleus. We report here that the majority of NPS-expressing neurons in the LC area and the principal sensory trigeminal nucleus are glutamatergic neurons, whereas many NPS-positive neurons in the lateral parabrachial nucleus coexpres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
280
4

Year Published

2009
2009
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 249 publications
(299 citation statements)
references
References 63 publications
15
280
4
Order By: Relevance
“…Comparison of the here identified murine NPS target neurons with the published rat NPSR expression patterns (Xu et al, 2007;Leonard and Ring, 2011) revealed that mouse and rat brain NPSR expression sites overlap largely but not completely. We found NPS target neurons in the murine basolateral and central amygdaloid nuclei, where no NPSR expression in the rat brain had been reported.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Comparison of the here identified murine NPS target neurons with the published rat NPSR expression patterns (Xu et al, 2007;Leonard and Ring, 2011) revealed that mouse and rat brain NPSR expression sites overlap largely but not completely. We found NPS target neurons in the murine basolateral and central amygdaloid nuclei, where no NPSR expression in the rat brain had been reported.…”
Section: Discussionmentioning
confidence: 84%
“…Even though, in rats, NPS expression is limited to three brain regions (the peri-locus coeruleus, the lateral parabrachial nucleus, and the principle sensory 5 nucleus of the trigeminus), NPSR mRNA (Xu et al, 2007) and protein (Leonard and Ring, 2011) are expressed throughout the rat brain. However, NPSR protein and mRNA expression patterns do not overlap completely, as in the case of the hippocampal CA1-3 regions and the dentate gyrus, leaving the ultimate identity of NPS target sites open.…”
Section: Introductionmentioning
confidence: 99%
“…Brain in situ hybridization revealed that the NPS peptide is expressed principally in a group of previously undescribed neurons located between the locus ceruleus (LC), the barrington, and the parabrachial nuclei. In the area between the LC and the barrington nucleus, NPS mRNA is predominantly expressed in glutamatergic cells, whereas in the parabrachial area, its expression overlaps that of corticotrophin releasing factor positive neurones (Xu et al, 2004(Xu et al, , 2007. NPS receptor mRNA is expressed throughout the central nervous system, with the highest concentration found in olfactory structures, in the amygdaloid complex, in the subiculum, in the lateral, dorsomedial and ventromedial hypothalamus, and in the paraventricular thalamic nucleus (Xu et al, 2004(Xu et al, , 2007.…”
Section: Introductionmentioning
confidence: 99%
“…In the area between the LC and the barrington nucleus, NPS mRNA is predominantly expressed in glutamatergic cells, whereas in the parabrachial area, its expression overlaps that of corticotrophin releasing factor positive neurones (Xu et al, 2004(Xu et al, , 2007. NPS receptor mRNA is expressed throughout the central nervous system, with the highest concentration found in olfactory structures, in the amygdaloid complex, in the subiculum, in the lateral, dorsomedial and ventromedial hypothalamus, and in the paraventricular thalamic nucleus (Xu et al, 2004(Xu et al, , 2007. Activation of NPSR by intracerebroventricular (ICV) injection of NPS evokes a unique pattern of responses, including stimulation of locomotor activity, increased arousal and suppression of all stages of sleep, but also decreased experimental anxiety (Reinscheid et al, 2005;Xu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Anatomically, both NPS precursor and receptor mRNAs are found predominately in the central nervous system (Xu et al, 2007). Functionally, central administration of NPS increases locomotor activity in both naïve and habituated mice, effects that are abolished in mice with a disruption of the NPSR (Duangdao et al, 2009).…”
Section: Introductionmentioning
confidence: 99%